2013
DOI: 10.1038/srep01915
|View full text |Cite
|
Sign up to set email alerts
|

Hadal disturbance in the Japan Trench induced by the 2011 Tohoku–Oki Earthquake

Abstract: In situ video observations and sediment core samplings were performed at two hadal sites in the Japan Trench on July, 2011, four months after the Tohoku–Oki earthquake. Video recordings documented dense nepheloid layers extending ~30–50 m above the sea bed. At the trench axis, benthic macrofauna was absent and dead organisms along with turbid downslope current were observed. The top 31 cm of sediment in the trench axis revealed three recent depositions events characterized by elevated 137Cs levels and alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
121
1
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 138 publications
(131 citation statements)
references
References 23 publications
6
121
1
3
Order By: Relevance
“…These acoustic characteristics are consistent with remotely operated underwater vehicle (ROV) observations made soon after the 2004 earthquakes (Ashi et al 2014). After the Tohoku-oki earthquake, Oguri et al (2013) also observed high turbidity in the bottom water of the Japan Trench, and Noguchi et al (2012) reported remobilization of surficial sediments triggered by the earthquake based on turbidity sensor monitoring and surface sediment sampling.…”
Section: Surficial Remobilization Triggered By Earthquakessupporting
confidence: 78%
See 1 more Smart Citation
“…These acoustic characteristics are consistent with remotely operated underwater vehicle (ROV) observations made soon after the 2004 earthquakes (Ashi et al 2014). After the Tohoku-oki earthquake, Oguri et al (2013) also observed high turbidity in the bottom water of the Japan Trench, and Noguchi et al (2012) reported remobilization of surficial sediments triggered by the earthquake based on turbidity sensor monitoring and surface sediment sampling.…”
Section: Surficial Remobilization Triggered By Earthquakessupporting
confidence: 78%
“…Understanding how these factors affect sediment remobilization is important for more precisely interpreting and correlating palaeoseismic events from seismo-turbidites. Suspended sediments with extremely high turbidity have been observed soon after earthquakes in several studies (Noguchi et al 2012;Oguri et al 2013;Ashi et al 2014). Although these high-turbidity plumes are assumed to be evidence for the remobilization of surface sediments, it is important to confirm this assumption.…”
mentioning
confidence: 99%
“…Nematodes may also be transported deep into the sediments by the bioturbation activity of macrofauna (Moodley et al, 2000), or through physical disturbance (Leduc and Pilditch, 2013). The vertical distribution of nematodes in the sediment may therefore provide an indicator for the degree of vertical sediment mixing and burial of organic matter occurring as a result of bioturbation or physical processes (such as turbidite flow) thought to be relatively common in trenches (Lambshead et al, 2001;Oguri et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…While it is relatively well described in current models, the role of episodic events has been long neglected because of the lack Frontiers in Marine Science | www.frontiersin.orgof observations and their unpredictability (Durrieu de Madron et al, 2011). Along the continental slope, earthquakes may generate landslides that affect deposition and, consequently, the benthic ecosystem (Oguri et al, 2013). Other events such as storms and river floods have been shown to dominate particle transport in key areas of the coastal zone which implies a large effect on community structuration and biogeochemical function.…”
Section: Episodic Events and Recoverymentioning
confidence: 99%